Nephrotic syndrome: Pretibial epidermolysis bullosa in a patient with CD151 tetraspanin defect: A case report - Almokali, Khamisa; Hissah Alshalawi; Marwh G. Aldriwesh; Alotibi, Raniah S. (International Journal of Health Sciences, 2023)
Nephrotic syndrome (NS)-epidermolysis bullosa (EB) sensorineural deafness syndrome is an autosomal recessive rare genetic disease caused by a CD151 gene homozygous mutation on chromosome 11p15.5. In this report, we discuss a rare case related to a Saudi patient with genetic syndrome who presented with NS and EB. Whole genome sequencing results indicated a homozygous pathogenic variant identified in the CD151 gene (c.493C>T p.(Arg165*), which was consistent with a genetic diagnosis of autosomal recessive nephropathy with pretibial EB and deafness syndrome. The findings emphasize that even a single genotype can result in variable phenotypic expression, necessitating the assessment of the pleiotropic effects of the disease on the patient, which can range from severe to mild. This case report adds to the literature by highlighting the considerable phenotypic variation that can be present in patients with the CD151 mutation.